THE INNER CONFLICT OF THE MAIN CHARACTER IN THE AVIATOR (2004) USING SIGMUND FREUD PERSPECTIVE - cut novita srikandi (STIBA IEC JAKARTA, 2017)
This study aimed to analyze the inner conflict of the main character in the movie entitled The Aviator. The Aviator takes the life story of world aviation named Howard Hughes. Howard Hughes is a young millionaire, entrepreneur, and also a movie director. He succeed seize his ambition at 24 years old. Freud's psychoanalysis approach used in analyzing the main characters is experiencing growth or personality changes dynamically. Changes and developments in the main characters' personalities due to their inner conflicts are complicated. The main character is kept up haunted by inner conflict, anxiety, and helplessness facing reality outside itself. Inner conflicts triggered by the sequences of events in the past, directly and indirectly influence or change the personality of the character. The inner conflict was traced and understood by using the theory of Freud's psychoanalysis.